2011
DOI: 10.1002/cbic.201100172
|View full text |Cite
|
Sign up to set email alerts
|

Abyssomicin Biosynthesis: Formation of an Unusual Polyketide, Antibiotic‐Feeding Studies and Genetic Analysis

Abstract: Small wonder: Atrop‐abyssomicin C is a small, yet complex spirotetronate (see scheme) that is active against Gram‐positive bacteria, such as MRSA. Feeding studies and genetic manipulation of its producer, Verrucosispora maris AB‐18‐032, for the first time give insight into its biosynthesis and demonstrate how closely related the members of this important class of molecules are.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 64 publications
0
58
0
3
Order By: Relevance
“…Comparison with other biosynthetic studies of tetronate antibiotics aided in the identification of genes responsible for abyssomicin C biosynthesis; three genes encoding for proteins for the generation of the polyketide backbone (which effectively forms the macrocycle in abyssomicin C); five genes encoding for proteins involved in the generation of the tetronate moiety; three genes for further oxidative enzymes; and a variety of other genes related to import, export and packaging of the molecule. 57 It was noted that the structure of 23 and 24 were similar to that of chorismate, a precursor to PABA, 58 and studies revealed that atrop-abyssomicin irreversibly binds the Cys263 of E. coli 4-amino-4-deoxychorismate in a Michael addition, forming a sulphur-bound abyssomicin D in the process. 47 This mechanism is attributed to the α,β-unsaturated ketone, which is not present in other detected abyssomicins.…”
Section: Abyssomicin C: a Promising Antibacterial For Tuberculosismentioning
confidence: 94%
“…Comparison with other biosynthetic studies of tetronate antibiotics aided in the identification of genes responsible for abyssomicin C biosynthesis; three genes encoding for proteins for the generation of the polyketide backbone (which effectively forms the macrocycle in abyssomicin C); five genes encoding for proteins involved in the generation of the tetronate moiety; three genes for further oxidative enzymes; and a variety of other genes related to import, export and packaging of the molecule. 57 It was noted that the structure of 23 and 24 were similar to that of chorismate, a precursor to PABA, 58 and studies revealed that atrop-abyssomicin irreversibly binds the Cys263 of E. coli 4-amino-4-deoxychorismate in a Michael addition, forming a sulphur-bound abyssomicin D in the process. 47 This mechanism is attributed to the α,β-unsaturated ketone, which is not present in other detected abyssomicins.…”
Section: Abyssomicin C: a Promising Antibacterial For Tuberculosismentioning
confidence: 94%
“…Based on a similar reaction which has been suggested for abyssomicin (Fig. 1B), 71 we propose that the cyclization resulting in this heterocyclic ring would proceed through two steps. First, the alkene present at C-14/C-15 in intermediate 12 would undergo an epoxidation giving intermediate 13.…”
Section: Biosynthesismentioning
confidence: 84%
“…PKS domains are shown as circles. Adapted from Gottardi et al (2011). which follow have the same basic set, each extended by DH and KR domains arranged in the biosynthetic assembly line. Module 5 of abyB2 has the same arrangement of module 4, but the DH and KR domains are likely to be inactive.…”
Section: Secondary Metabolites Synthesised By Pks Gene Clustermentioning
confidence: 99%
“…There are also genes encoding oxygenases, as well as genes with putative regulatory and export functions involved in the abyssomicin biosynthesis. Formation of abyssomicin C requires two propionates, five acetates and one glucose-derived metabolite (Gottardi et al, 2011).…”
Section: Secondary Metabolites Synthesised By Pks Gene Clustermentioning
confidence: 99%
See 1 more Smart Citation